2021
DOI: 10.1021/acs.nanolett.1c01944
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms in Vertically Aligned Dense Nanowire Arrays

Abstract: Nanowires are an increasingly prevalent class of nanomaterials in composites and devices, with arrays and other complex geometries used in various applications. Little investigation has been done regarding the mechanical behavior of micron-sized nanowire structures. We conduct in situ microcompression experiments on vertically aligned dense microbundles of 300 nm diameter single-crystalline zinc oxide nanowires to gain insights into their structural failure. Experiments demonstrate that bundles containing appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For example, free-standing vertically aligned nanowires of Si, ZnO, GaAs, and InP have achieved excellent performance in various optoelectronic fields. 7 11 However, the growth of free-standing vertically aligned MHP nanowire arrays is difficult. Compared with the numerous studies on growth of horizontal MHP nanowire arrays, 2 , 12 17 there are only a few reports of vertically aligned nanowire arrays, and those mostly concern nanowires physically confined inside various templates such as anodized aluminum oxide (AAO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, free-standing vertically aligned nanowires of Si, ZnO, GaAs, and InP have achieved excellent performance in various optoelectronic fields. 7 11 However, the growth of free-standing vertically aligned MHP nanowire arrays is difficult. Compared with the numerous studies on growth of horizontal MHP nanowire arrays, 2 , 12 17 there are only a few reports of vertically aligned nanowire arrays, and those mostly concern nanowires physically confined inside various templates such as anodized aluminum oxide (AAO).…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskite (MHP) nanowire arrays have shown excellent performance in optoelectronic applications such as lasers, LEDs, solar cells, and photodetection. Vertically aligned nanowire arrays offer several advantageous properties, such as enhanced optical absorption and emission along the direction orthogonal to the substrate, which is essential for solar cells and light-emitting diodes, as well as technical advantages including higher nanowire density and scalable device processing. For example, free-standing vertically aligned nanowires of Si, ZnO, GaAs, and InP have achieved excellent performance in various optoelectronic fields. However, the growth of free-standing vertically aligned MHP nanowire arrays is difficult. Compared with the numerous studies on growth of horizontal MHP nanowire arrays, , there are only a few reports of vertically aligned nanowire arrays, and those mostly concern nanowires physically confined inside various templates such as anodized aluminum oxide (AAO). A few studies have reported free-standing MHP nanowires by solution extrusion and vapor–liquid–solid methods, but the alignment of the obtained NWs was not satisfactory.…”
Section: Introductionmentioning
confidence: 99%